Dynamics of the South China Sea Dispute: Indonesia’s Position in Multilateral Diplomacy and the Enforcement of UNCLOS 1982 - Andin Wisnu Sudibyo; Richard (al-Battar: Jurnal Pamungkas Hukum, 2025)
The South China Sea constitutes a strategically significant global region due to its vital role in international trade, natural resource potential, and regional geopolitical stability; however, it also remains a complex maritime dispute area arising from overlapping claims by several states, particularly China’s unilateral nine-dash line claim, which is inconsistent with the provisions of the United Nations Convention on the Law of the Sea (UNCLOS) 1982. Although Indonesia is not a direct claimant state, it possesses substantial strategic interests in safeguarding sovereignty, maritime security, and legal certainty under international law, especially with regard to its Exclusive Economic Zone (EEZ) in the North Natuna Sea. This study aims to analyze the dynamics of the South China Sea dispute from an international law perspective by focusing on Indonesia’s position in multilateral diplomacy and the enforcement of UNCLOS 1982. Employing a qualitative descriptive-analytical method, this research is based on doctrinal legal analysis of primary, secondary, and tertiary legal materials, including UNCLOS 1982, the 2016 arbitral award in Philippines v. China, official ASEAN documents, and contemporary scholarly literature. The findings indicate that while UNCLOS 1982 provides a clear and binding legal framework for maritime dispute settlement, its implementation faces significant challenges due to political considerations and geopolitical power dynamics. Indonesia consistently emphasizes the primacy of international law, strengthens multilateral diplomacy through ASEAN, and actively promotes the establishment of a legally binding Code of Conduct, thereby affirming its role as a normative actor contributing to regional stability and the enforcement of the international law of the sea.